2003
DOI: 10.1103/physrevlett.91.157406
|View full text |Cite
|
Sign up to set email alerts
|

Light-Emitting Field-Effect Transistor Based on a Tetracene Thin Film

Abstract: We report the first organic light-emitting field-effect transistor. The device structure comprises interdigitated gold source and drain electrodes on a Si/SiO(2) substrate. A polycrystalline tetracene thin film is vacuum sublimated on the substrate forming the active layer of the device. Both holes and electrons are injected from the gold contacts into this layer leading to electroluminescence from the tetracene. The output characteristics, transfer characteristics, and the optical emission properties of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
436
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(448 citation statements)
references
References 14 publications
5
436
0
5
Order By: Relevance
“…It should be noted that the device architecture for devices on QW1 and QW2 substrates is complex, since the devices contain more than one p-n junction. The contact geometry has some similarity with the light-emitting transistors, [38][39][40] which also include devices with layered electron and hole transporting layers with two contacts deposited on the top of the device. 40 While our devices do not have gate electrode for additional modulation of the charge injection and light emission, it has been shown that the light emission in a light emitting transistor can occur at certain drain-source bias voltages independent on the gate voltage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the device architecture for devices on QW1 and QW2 substrates is complex, since the devices contain more than one p-n junction. The contact geometry has some similarity with the light-emitting transistors, [38][39][40] which also include devices with layered electron and hole transporting layers with two contacts deposited on the top of the device. 40 While our devices do not have gate electrode for additional modulation of the charge injection and light emission, it has been shown that the light emission in a light emitting transistor can occur at certain drain-source bias voltages independent on the gate voltage.…”
Section: Resultsmentioning
confidence: 99%
“…40 While our devices do not have gate electrode for additional modulation of the charge injection and light emission, it has been shown that the light emission in a light emitting transistor can occur at certain drain-source bias voltages independent on the gate voltage. 38 Thus, complex device architectures can have practical relevance even though they are more complicated to understand compared to simple p-n junctions. It should also be noted that the top p-GaN layer in QW1 and QW2 devices is very thin (of the order 100-200 nm), so that at larger bias, the current spread is expected to include MQW area.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Light-emitting properties of organic FETs have also been reported. 4,5 The studies of charge carriers in these devices are of fundamental importance in understanding the basic physical processes, such as carrier injection, accumulation, and transport, and hence, may contribute to the formulation of the design principle of highly efficient devices. However, intrinsic transport properties in the devices tend to be masked due to the molecular disorders at the device interfaces.…”
mentioning
confidence: 99%
“…Recently, a unipolar lightemitting OFET based on tetracene was reported. [12][13][14] However, in unipolar devices, light emission is restricted to a region very close to the contact that injects the charge carriers of the lower mobility. In contrast, an ambipolar lightemitting transistor would allow the electron-hole balance as well as the location of the recombination zone between source and drain electrodes to be tuned by the gate voltage, hence improving the quantum efficiency.…”
mentioning
confidence: 99%